Cold Atmospheric Pressure Plasma Jet for the Improvement of Wettability of Polypropylene. (20th June 2020) - Baniya, Hom Bahadur; Guragain, Rajesh Prakash; Baniya, Binod; Subedi, Deepak Prasad
Abstract : This paper reports the generation of cold plasma jet working under atmospheric pressure condition, for surface treatment of polymeric films. The discharge has been characterized by electrical and optical methods. The electrical property of the discharge has been studied by taking current-voltage wave forms using voltage and current probes. The production of argon plasma jet is done in atmospheric conditions which are relatively much cheaper, convenient, and safer to use. The atmospheric pressure plasma jet sustained in pure argon has been used to improve wettability of polypropylene (PP). Cold atmospheric pressure plasma jet (CAPPJ) has been generated by a high-voltage power supply (5.5 kV, 0-20 kV) at an operating frequency of 20 kHz. The surface properties of the controls and plasma-treated PP samples were characterized by contact angle measurement, surface free energy measurement, scanning electron microscopy, and the Fourier transform-infrared spectroscopy analysis.